Fake News and World Alienation: Reflections on Bolsonaro’s Presidential Campaign - Dias, Thiago (HannahArendt.net, 2021)
I outline here a still tentative approach to a central question of our time: how do new communication technologies and their politics affect the political? Jair Bolsonaro's use of Whatsapp in his victorious electoral campaign and in his first 18 months of government serve here as example and source of reflection. In this approach, which is still tentative, Arendt's notion of world alienation is highlighted because it makes possible to point at a difference between public appearance and the images that form our digital life. For Arendt, as one knows, the world has appearance and a thing-character, which bestows it with an objectivity; compared to the objects and appearance of the world, the fluid character of the images becomes particularly prominent, and that makes it easier to show why even the most absurd fake news can easily find people prone to believe them. Social media did not invent images, but took them to a greater degree of control and took people to a greater degree of alienation, and Bolsonaro knew how to use them by bringing to the public all the fluidity of the images, which resulted in an enormous electoral force and in a great capacity to destroy institutions.